(untitled) (Texas Journal of Engineering and Technology, 2026)
This article studies the issue of developing effective mechanisms for mandatory reduction of vehicle speed on mountainous roads. The mountainous areas of the M-39 international highway, passing through the Jizzakh region, within the range of 982–1013 km, were selected as the object of research. During the study, factors affecting the turning radius of the road, longitudinal slope, width of the carriageway, traffic flow intensity, speed, pavement condition and accident probability were studied. A methodology for setting an adaptive speed limit by assessing road geometry, traffic flow parameters and external environmental factors based on a single integrated risk index was proposed